On the delineation of tropical vegetation types with an emphasis on forest/savanna transitions - Torello-Raventos, Mireia; Feldpausch, Ted R.; Veenendaal, Elmar M.; Schrodt, Franziska; Saiz, Gustavo; null, Tomas; Djagbletey, Gloria Djaney; Ford, Andrew J.; Kemp, Jeanette E.; Marimon, Beatriz Schwantes; Marimon Júnior, Ben Hur; Lenza, Eddie; et al. (Plant Ecology and Diversity, 2013)
Background: There is no generally agreed classification scheme for the many different vegetation formation types occurring in the tropics. This hinders cross-continental comparisons and causes confusion as words such as 'forest' and 'savanna' have different meanings to different people. Tropical vegetation formations are therefore usually imprecisely and/or ambiguously defined in modelling, remote sensing and ecological studies.Aims: To integrate observed variations in tropical vegetation structure and floristic composition into a single classification scheme.Methods: Using structural and floristic measurements made on three continents, discrete tropical vegetation groupings were defined on the basis of overstorey and understorey structure and species compositions by using clustering techniques.Results: Twelve structural groupings were identified based on height and canopy cover of the dominant upper stratum and the extent of lower-strata woody shrub cover and grass cover. Structural classifications did not, however, always agree with those based on floristic composition, especially for plots located in the forest-savanna transition zone. This duality is incorporated into a new tropical vegetation classification scheme.Conclusions: Both floristics and stand structure are important criteria for the meaningful delineation of tropical vegetation formations, especially in the forest/savanna transition zone. A new tropical vegetation classification scheme incorporating this information has been developed. © 2013 Copyright 2013 Botanical Society of Scotland and Taylor & Francis.